Process optimization in citric acid production using sewage sludge as fermentation media - Mohamad Hanapi, Nur Hanis; Alam, Md. Zahangir; Abdulkarim, Mohd Ismail (2011)
A research has been conducted on liquid state bioconversion for the production of citric acid using Sewage Treatment Plant (STP) sludge as main substrate and added with sucrose as co-substrate. Three parameters were examined as to determine the best process optimization conducted in two liter (2L) bioreactor. Two level factorial designs with three parameters are applied for the fermentation. It was carried out using local isolates Aspergillus niger strain O103A at room temperature (30-32oC), agitation is set at three different values which are 100, 200 and 300rpm. Initial pH for fermentation is set at 5 and it was further adjusted to three levels which are 2, 3, and 4 on the second day of the fermentation. Another parameter is aeration where 1, 1.5 and 2 vvm were introduced. The fermentation was carried out for five days. The maximum yield of citric acid obtained throughout the fermentation is 23.68 g/L, which is due to low pH, low agitation and high aeration values.